Le Carte Kanzler-Vannutelli dell'Archivio Vaticano: inventario - Polselli, Vanessa (Collectanea Archivi Vaticani, 2013)
The "Fondo Kanzler-Vannutelli" (originally 90 archive items covering the years between 1824-1906) constitutes a series of documents that belonged to the German general Hermann Kanzler (1822-1888), the last commander of the Papal Army and Pro-Minister of Arms under Pope Pius IX. Additionally, the fondo contains letters and diaries of his brother-in-law, the Dominican friar Vincenzo Vannutelli (1841-1900), cousin of the better-known Cardinal Vincenzo Vannutelli. Friar Vannutelli was a unique religious personage who was a tireless promoter of unity between the Roman Catholic Church and the Eastern Churches.-- Supplied by publisher